2014
DOI: 10.1158/0008-5472.can-14-0612
|View full text |Cite
|
Sign up to set email alerts
|

CCR5 Receptor Antagonists Block Metastasis to Bone of v-Src Oncogene–Transformed Metastatic Prostate Cancer Cell Lines

Abstract: Src family kinases (SFKs) integrate signal transduction for multiple receptors, regulating cellular proliferation invasion and metastasis in human cancer. Although Src is rarely mutated in human prostate cancer, SFK activity is increased in the majority of human prostate cancers. In order to determine the molecular mechanisms governing prostate cancer bone metastasis, FVB murine prostate epithelium was transduced with oncogenic v-Src. The prostate cancer cell lines metastasized in FVB mice to brain and bone. G… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
91
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 67 publications
(95 citation statements)
references
References 39 publications
1
91
1
Order By: Relevance
“…Stimulation of cancer cells with recombinant CCL5, IL-6, or CXCL10 was able to induce glycogen mobilization. Several studies have established a role for CCL5 in the promotion of metastasis (; Mitra et al, 2012; Sicoli et al, 2014) and while CCL5 secretion was not p38-dependent in our study, CCL5 still plays a role in CAF-mediated glycogen mobilization. It is likely that the unique combination of chemo/cytokines produced by CAFs is required for full stimulation of glycogen mobilization and subsequent metastasis.…”
Section: Discussioncontrasting
confidence: 44%
“…Stimulation of cancer cells with recombinant CCL5, IL-6, or CXCL10 was able to induce glycogen mobilization. Several studies have established a role for CCL5 in the promotion of metastasis (; Mitra et al, 2012; Sicoli et al, 2014) and while CCL5 secretion was not p38-dependent in our study, CCL5 still plays a role in CAF-mediated glycogen mobilization. It is likely that the unique combination of chemo/cytokines produced by CAFs is required for full stimulation of glycogen mobilization and subsequent metastasis.…”
Section: Discussioncontrasting
confidence: 44%
“…Several independent groups have observed that CCR5 was expressed by some types of cancer cells including breast [31], prostate [32], and gastric cancer [33]. Furthermore, in these studies, maraviroc directly inhibited the in vivo invasiveness of these cancer cells and reduced subsequent tumor progression.…”
Section: Discussionmentioning
confidence: 99%
“…As CCR5 was identified as a co-receptor mediating the entry of macrophage-tropic HIV [20], the CCR5 antagonist maraviroc has been approved for the treatment of patients with CCR5-tropic HIV infection [48]. However, with increasing evidence for the contribution of CCR5 to cancer progression, maraviroc has been shown to suppress metastasis of breast and prostate cancers in mice [26,28] and to achieve an objective clinical response in patients with advanced-stage metastatic colorectal cancer [29]. Combined with these reports, the current work suggests tumor-promoting effects of CCR5 in a broad range of cancer types, indicating the potential of CCR5 as a common target for cancer therapy.…”
Section: Discussionmentioning
confidence: 99%